Pengembangan Sistem Informasi Support and Maintenance Berbasis Web pada Pengadilan Negeri Makassar Kelas IA Khusus - M Syahid Nur Wahid; Kelvianto Pratama Harum; Muhammad Alif Leo; Putri Nandasari; Andi Muh Achyar AM (Sakura Publisher, 2023)
Makassar Class IA Special District Court is a first-level judicial institution located in Makassar City, South Sulawesi. This institution uses electronic devices and computers in its daily operations. However, the complaint system and electronic and computer processing still use the conventional method of manually recording and reporting complaints made. To overcome these problems, a